Production of beta-keratin from chicken feathers - Siti Aisyah Radhiah, Mohamed (2013)
The concept of the business of K-my Sdn Bhd is a process of turning waste feathers from poultry industry into a high value product for use in the cosmetics and consumer goods industries, particularly hair-care and hair treatment. There are a few problems that become the reason for K-my Sdn Bhd has potential to become one of the most successful companies in Malaysia. It is because the production of keratin protein from sheep wool caused high cost. It is due to the price of sheep wool is quite expensive. Besides, sheep wool availability in Malaysia is limited. So, the researchers need to find other alternative as a new raw material. On the other hand, the demand of product based on keratin protein is increased. Due to availability, chicken feather is easy to find in Malaysia. The production of chicken feather in Malaysia is too high until causing the environmental problem. Based on these problems, K-my Sdn Bhd take this advantage to produce a product that is cheap but has a lot of benefits. The demand of the keratin in Malaysia is increasing every year. It is due to the demand of the cosmetic and toiletries are increasing as well. The market of keratin is contributes 5% in the cosmetic and toiletries industry. The demand of keratin in 2012 is 3465 MT per year. The market size of the keratin also increases by year. The invention relates to a process for extracting keratin from poultry feather, and provides a quicker process thus allowing large-scale productions of the keratin to be carried out untimely, efficient and productive manner. The main processes are dissolving chicken feathers and separation of proteins. Keraplast Technologies is the world’s leading innovator of keratin protein technology which was established on 1996 by using the sheep wools as the raw materials. K-My Sdn Bhd has assembled a management team experienced in keratin, research and development, marketing, management and finance. Assoc Prof Dr Arun Gupta, Chief Executive Officer, currently works as a associate professor at Universiti Malaysia Pahang in Faculty of Chemical and Natural Resources Engineering. He is expert in research and development about keratin, and got a lot of award about his project. Moreover, Siti Nur Khairunisa who is appointed to be a production manager is one of researchers that do the research about beta-keratin from chicken feathers. Currently she is a Master student of Universiti Malaysia Pahang. The start up business of K-my Sdn. Bhd needs the capital about RM 2.5 million. The cash is to buy the equipments, land, building, contingency plan, and the other expenses including buying the raw materials and paying the salaries to the employers and employees. The funds will be get from the bank and Malaysia Debt Venture berhad (MDVB).